Japanese ethnographies of the Pacific: Language, politics and perspective. Issue 2 (1st October 2019) - Maggio, Rodolfo
AbstractAn increasing number of Japanese ethnographers have conducted fieldwork research in Pacific Islands in the last few decades, which has resulted in a growing corpus of ethnographic literature. This is partly related to the historical role that Japan has played in the Pacific and partly to its geographical proximity to the area. While this geo-historical advantage combines with the availability of ethnographic works produced by non-Japanese scholars, the latter remain largely unable to access anthropological literature only available in Japanese. This not only limits the international circulation of ethnographies produced by Japanese anthropologists of the Pacific, but also the possibility of engaging with a larger body of anthropological traditions and, thus, with the overall project of 'World Anthropologies'. This article discusses the reasons why Japanese ethnographies of the Pacific provide not only a technical advantage for non-Japanese scholars of Pacific Islands but also a qualitative difference in terms of anthropological perspectives. In particular, it examines the differential impact of different colonial and postcolonial debates on Japanese and anglophone anthropology in relation to ethnographies of urban Melanesia.